Efficienza tecnologica e produttiva delle strutture trasfusionali in Italia - Cornago, Dante; Garattini, Livio (Farmeconomia. Health economics and therapeutic pathways, 2002)
In all the developed countries the methods of blood collection and production are relevant subjects for the pharmacoeconomics studies, because of their health and economic implications related to the health policies in this area. The “blood market” rappresents an area where the sanitary items, the economic items and also the ethic items must be broached at the same time; therefore it can be considered emblematic. By this situation arises Progetto CO.R.SA. (COsti Raccolta SAngue), a project for estimating productivity and cost for a representive sample of italian trasfusional structure (ST). The study is supported by Società Italiana di Medicina Trasfusionale e Immunoematologia (SIMTI). In Italy there are about 380 ST, but only 30 ST resulted suitable for the study. The analysis investigates six rates concerning: a) wastes; b) technological efficiency; c) personnel productivity. The present work describes only the informations on ST organization and production, delaying the results about costs to a specific further report.